DEVELOPMENT OF LIPOPOLYSACCHARIDE-POLYOXIDONIUM COMPLEXES AND CONJUGATES AGAINST THE Q FEVER DISEASE FOR APPLICATION PURPOSE OF VACCINE PROTOTYPE - Arayici, Pelin Pelit; Acar, Tayfun; Karahan, Mesut; Derman, Serap; Mustafaeva, Zeynep; Toman, Rudolf (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2020)
Coxiella burnetii is a Gram-negative bacteria that causes Q fever, a common zoonotic disease worldwide. The Coxiella burnetii LPS (Lipopolysaccharides) membrane is a dominant antigen in the immune system and has an important role in creating a new generation vaccine against Q fever. Polyoxidonium is a water-soluble, synthetic, nontoxic, biocompatible polymer, as used an immunoadjuvant. New generation vaccines are more advantageous than other vaccines since they do not contain the whole virus, no side effects are expected, and they generate a stronger immune response with safe and effective adjuvant polymers. The study presented as a new vaccine candidate against Q fever is covered findings of the complexes and conjugates synthesized in different ratios of LPS and Polyoxidonium. The synthesized complexes and conjugates were characterized by GPC and ZetaSizer, upon optimum ratio was detected. Immune responses were investigated by immunization of mice with selected complex and conjugate. Obtained results show that LPS-polymer complexes and conjugates have
Keywords: Q Fever; Polyoxidonium; ternary complexes; conjugation; immunization; ELISA; COXIELLA-BURNETII; PEPTIDE; Environmental Sciences & Ecology